2021
DOI: 10.1177/15330338211056809
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a circRNA-miRNA-mRNA Regulated Pathway Involved in EGFR-TKI Lung Adenocarcinoma Resistance

Abstract: Objectives: Epidermal growth factor receptor-tyrosine kinase inhibitors are widely used for lung epidermal growth factor receptor-positive lung adenocarcinomas, but acquired resistance is inevitable. Although non-coding RNAs, such as circular RNA and microRNA, are known to play vital roles in epidermal growth factor receptor-tyrosine kinase inhibitor resistance, comprehensive analysis is lacking. Thus, this study aimed to explore the circular RNA-microRNA-messenger RNA regulatory network involved in epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Nevertheless, till now, research on the function of circRNAs in NSCLC with gefitinib resistance is still limited. In this study, we focused on circ_0091537, which was previously shown to be upregulated in lung cancer tissues with gefitinib resistance [8]. The data suggested that circ_0091537 dysregulation might be associated with gefitinib resistance in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, till now, research on the function of circRNAs in NSCLC with gefitinib resistance is still limited. In this study, we focused on circ_0091537, which was previously shown to be upregulated in lung cancer tissues with gefitinib resistance [8]. The data suggested that circ_0091537 dysregulation might be associated with gefitinib resistance in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With the advance of RNA sequencing technology, an increasing number of circRNAs are identified, and their functions are preliminarily disclosed. Circ_0091537 was previously recorded to be highly expressed in lung cancer cells with gefitinib chemoresistance [8], hinting that circ_0091537 might be involved in NSCLC progression. However, the underlying role of circ_0091537 in NSCLC with gefitinib chemoresistance is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary circRNA/lncRNA-miRNA–mRNA networks have been constructed to shed light on the role of ncRNAs in regulating signaling pathways and drug resistance. 407 …”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%
“…Preliminary circRNA/lncRNA- miRNA-mRNA networks have been constructed to shed light on the role of ncRNAs in regulating signaling pathways and drug resistance. 407 Given the complicated and delicate regulatory mechanisms of ncRNAs and their involvement in regulating multiple pathways, ncRNAs are promising therapeutic targets. Some ncRNA drugs have been used in clinical trials but not for treating TKI-resistant tumors.…”
Section: Epigenetic Modificationmentioning
confidence: 99%
“…In our previous study, we found that circ7312 and MAPK1 were highly expressed in EGFR-TKIresistant PC9 cells but were lowly expressed in the EGFR-TKI-sensitive PC9/ER cells. We also found that the circ7312/miR-764/MAKP1 axis is involved in the development of EGFR-TKI resistance [19]. Therefore, in this study, we aimed to determine the underlying mechanism of this axis in pyroptosis and apoptosis that is involved in EGFR-TKI resistance.…”
Section: Introductionmentioning
confidence: 95%